EFEKTIVITAS PENERAPAN UNDANG-UNDANG ITE TERHADAP PELAKU PENYEBARAN HOAKS COVID-19 DI MEDIA SOSIAL - Zulfan; Lestari AKA; Dewi Maya Sari (Puslatbang KHAN, 2020)
The spread of hoaxes related to Covid-19 is increasingly happening, along with the increase in cases of the virus in Indonesia. This is confirmed by data from the Ministry of Communication and Informatics which found around 1,197 hoax issues related to Covid-19 spread across 4 digital platforms. Various efforts have been made by the Indonesian government to reduce the spread of hoaxes in society. One of them is by trapping the perpetrators of hoax spreading using the ITE Law. This study aims to determine the Effectiveness of the Implementation of the ITE Law on the Perpetrators of the Spread of the Covid-19 Hoax on Social Media. The method used in this research is library research method, which is a research method that utilizes library sources in obtaining research data. The type of data used is secondary data. The results of this study conclude that the Law of the Republic of Indonesia Number 19 of 2016 concerning Electronic Information and Transactions has not been effective in ensnaring the criminal act of spreading fake news or hoaxes related to Covid-19 through digital platforms in Indonesia. This law also does not fully accommodate cases related to false or hoax information.